Ocimum Gratissimum Linn. Leaf Extract and Fractions Pre-Treatments are not Associated With Deleterious Electrocardiogram Changes in Trastuzumab-Intoxicated Wistar Rats - A. Adeneye, Adejuwon; E. Olorundare, Olufunke; A. Adejumobi, Olumuyiwa; O. Omobowale, Temidayo; O. Akinsola, Akinyele; M. Ajayi, Abayomi (Al-Nahrain Journal of Science, 2024)
Trastuzumab (TZM) treatment is known to be associated with arrhythmogenic potential which primarily is the basis for its cardiotoxicity. The purpose of this study was to investigate the acute influence of oral pretreatments with 100 mg/kg/day of Ocimun gratissimum ethanolic leaf extract (OG) and its fractions (petroleum ether, PEOG; ethyl acetate, EAOG; and ethanolic extract, EOG) as well as valsartan-lisinopril fixed dose combination (VAL-LSP) on electrocardiogram (ECG) of Wistar rats intaperitoneally treated with 2.25 mg/kg/day TZM for 7 days.  Young adult male Wistar rats were randomly allotted into 12 groups of 6 rats per group. The rats were subjected to electrocardiograms (ECG) measurement using non-invasive procedures on days 1 and 7 of the experiment. Results showed that oral pretreatment with OG and its fractions (except EOG) as well as VAL-LSP fixed dose combination did not cause any remarkable changes in the ECG patterns of TZM-treated rats indicating that their relative oral safety in TZM chemotherapy. On the other hand, EOG pretreatment caused significant shortening of the OT/QTc interval in the TZM-treated rats highlighting the arrhthymogenic potential of this fraction. Overall, the study highlighted the arrhythmogenic potential of EOG in TZM chemotherapy while OG and its other solvent fractions as well as VAL-LSP could be considered relatively safe for use as adjuvants in TZM chemotherapy.